Crystal structures of human CK2α2 in new crystal forms arising from a subtle difference in salt concentration. Issue 5 (2nd May 2018) - Tsuyuguchi, Masato; Nakaniwa, Tetsuko; Kinoshita, Takayoshi
Abstract : New crystal forms of human CK2α2 were discovered and one showed improved crystallographic resolution to a maximum of 1.89 Å. Abstract : The catalytic subunits of protein kinase CK2 are classified into two subtypes: CK2α1 and CK2α2. CK2α1 is an attractive drug‐discovery target for various diseases such as cancers and nephritis. CK2α2 is defined as an off‐target of CK2α1 and is a potential target in the development of male contraceptive drugs. High‐resolution crystal structures of both isozymes are likely to provide crucial clues for the design of selective inhibitors of CK2α1 and/or CK2α2. To date, several crystal structures of CK2α1 have been solved at high resolutions of beyond 1.5 Å. However, crystal structures of CK2α2 have barely achieved a low resolution of around 3 Å because of the formation of needle‐shaped crystals. In this study, new crystal forms were exploited and one provided a crystal structure of CK2α2 at 1.89 Å resolution. This result, together with the structure of CK2α1, will assist in the development of highly selective inhibitors for both isozymes.